Bridging the students’ ability gap to create a conducive atmosphere in learning English through various communication activities - Aminah (Center for Humanities and Innovation Studies, 2018)
This study aims to get a detailed reason for collaborative communication activities in bridging the gaps in the perspective of the students in the classroom condition to create a conducive atmosphere in learning English. This study applied explorative qualitative study. The participants of this study are the second-semester students of English Literature Program in one of the universities in Makassar, South Sulawesi Indonesia. The data were collected through Myres-Briggs online questionnaire, interview, and classroom observation. The results of data analysis showed that the collaborative communication activities which can bridge the students’ gaps in their perspectives should be fun and collaborative. Also, this study showed that varied activities could be applied alternately in learning interaction and adjusted with the material taught with attractive teaching media. By the gap issue, it was also found that distinctive personality and personal interests caused the gap. This study also found classroom conditions in students’ point of view which could create conducive atmosphere physically and psychologically in learning English.